Enhancing support for the mental wellbeing of parents of children with a disability: Developing a resource based on the perspectives of parents and professionals. Issue 4 (2nd October 2018) - Gilson, Kim-Michelle; Davis, Elise; Corr, Lara; Stevenson, Shawn; Williams, Katrina; Reddihough, Dinah; Herrman, Helen; Fisher, Jane; Waters, Elizabeth
ABSTRACT: Background: Raising a child with a disability can place significant strain on the mental wellbeing of parents and carers. This study developed a mental wellbeing resource specifically for parents and carers of children and adolescents with a disability. Methods: Interviews with 20 parents and carers and 13 health and disability service professionals were conducted to determine resource content and format. Results: Key information areas for the resource were information about parent/carer wellbeing; understanding the barriers to wellbeing, including lack of support, being unable to ask for help, being isolated from the community, and having insufficient time or income to spend on self; suggestions on how to organise respite; and opportunities for increasing wellbeing. Conclusions: Given parental mental health is key to the quality of life of the child and family, it is recommended that the resource is distributed to parents and professionals, and adapted for different cultural and linguistic backgrounds.